Perspectives for energy development in Poland and in the European Union in the context of the European Green Deal: renewable energy and energy efficiency - Szczubełek, Grzegorz (Olsztyn Economic Journal, 2022)
The European Green Deal is a development strategy which aims to transform the European Union into a climate-neutral area by 2050. Due to the scale of reforms it envisages, it is considered the largest legislative initiative in the history of the European Union. The research aims to analyse the prospects for energy development in Poland and in the European Union in the context of the European Green Deal, with a particular focus on potential ways to increase the share of renewable energy sources and improve energy efficiency. Given the highly disparate environmental and socio-economic conditions, a number of EU countries will find it challenging to meet the ambitious requirements of the European Green Deal. Additionally, considering the huge impact of the Coronavirus pandemic and the war between Russia and Ukraine, the use of a sustainable energy security concept seems justified, as it takes into account the socio technical specificities of individual states. A predictable energy and climate policy consistent with the EU’s objectives may facilitate Poland’s fair transition towards sustainable development.